2010
DOI: 10.1111/j.1365-2591.2009.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dentine‐bonding agents on substance P release in human dental pulp

Abstract: Dentine-bonding agents placed over Class V cavity preparations increased SP release. One-step dentine-bonding agents increased SP release most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Neuropeptides were extracted by adding 150 mL of 0.5 mol/L of acetic acid and double boiling in a thermostat bath for 30 minutes in accordance with previously reported protocols (19)(20)(21)(22). SP and CGRP expression were determined by competition binding assays using human SP and human CGRP-radioimmunoassay (RIA) kits (RK-061-05 and RK-015-02; Phoenix Peptide Pharmaceutical, Belmont, CA).…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Neuropeptides were extracted by adding 150 mL of 0.5 mol/L of acetic acid and double boiling in a thermostat bath for 30 minutes in accordance with previously reported protocols (19)(20)(21)(22). SP and CGRP expression were determined by competition binding assays using human SP and human CGRP-radioimmunoassay (RIA) kits (RK-061-05 and RK-015-02; Phoenix Peptide Pharmaceutical, Belmont, CA).…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Neuropeptide was extracted by adding 150 mL of 0.5 mol/L acetic acid and double boiling in a thermostat bath for 30 minutes in accordance with previously reported protocols (11)(12)(13)(14)(15)(16).…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Neuropeptides were extracted by adding 150 mL 0.5 mol/L À1 acetic acid and double-boiling in a thermostat bath for 30 minutes in accordance with previously reported protocols (11,12,(16)(17)(18).…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…In dental pulp, it has been reported that its expression increases with carious progression (15) and with restorative procedures such as tooth bleaching (16), cavity preparation (17), and dentin bonding (18). SP has also been implicated during periodontal ligament inflammatory process (13,19,20).…”
mentioning
confidence: 99%